2012
DOI: 10.4018/jghpc.2012010103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Evaluation of a New Algorithm Based Fault Tolerance for Computing Systems

Abstract: In this paper, the authors present a new approach to algorithm based fault tolerance (ABFT) for High Performance computing system. The Algorithm Based Fault Tolerance approach transforms a system that does not tolerate a specific type of fault, called the fault-intolerant system, to a system that provides a specific level of fault tolerance, namely recovery. The ABFT techniques that detect errors rely on the comparison of parity values computed in two ways, the parallel processing of input parity values produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Investigations on TFET show interesting variations of drain current when there are K due to differnt biomolecules involved (23). This study examined the effect that biomolecule immobilisation has on the transistors nanocavity.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations on TFET show interesting variations of drain current when there are K due to differnt biomolecules involved (23). This study examined the effect that biomolecule immobilisation has on the transistors nanocavity.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-agent system models were first introduced and used to control the components of smart grids (7), which are most commonly used for large area grids. An example is the use of these models in intelligent energy markets (8)(9)(10)(11)(12)(13)(14)(15)(16). The multi-agent system is a new computational model in which several inputs interact with other inputs in an environment (10,17).…”
Section: Research Backgroundmentioning
confidence: 99%
“…A multi-agent system model is discussed in literature [15][16][17][18]21] for managing a distribution system comprising a large number of electric vehicles. The main reason is the use of the power system and, this agent modifies the program with the control and study of the network and informs them.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In the literature, several theories postulated after investigations by researchers and reported human factors to have had an impact on user behavior, both negative and positive which is mentioned by researchers and security experts have reported that the "weakest link" in any security chain is human behavior; because any technical security solution is still prone to failures due to human error [12]. From a practical perspective, understanding such behaviors is important; if users do not comply with information security solutions; however, technically sophisticated, lose their effectiveness [13]. Therefore, it is recognized that in the field of information security, reducing the risk requires attention to human aspects along with technological aspects.…”
Section: Introductionmentioning
confidence: 99%